2017
DOI: 10.1186/s13071-017-2497-6
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniasis in northwestern Saudi Arabia: identification of sand fly fauna and parasites

Abstract: BackgroundCutaneous leishmaniasis (CL) is a vector-borne disease transmitted by the bite of an infected sand fly. This disease is highly prevalent in Saudi Arabia where Leishmania major and L. tropica are the etiological agents. In the region of Hail, northwestern of Saudi Arabia, the incidence is about 183 cases/year. However, the epidemiology of the disease in this area is not well understood. Thus, an epidemiological survey was conducted in 2015–2016 to identify the circulating parasite and the sand fly fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 41 publications
(37 reference statements)
2
31
0
1
Order By: Relevance
“…Saudi Arabia is another important focus of CL (89), with most cases occurring in southwest, central, and eastern parts of the country. L. tropica is mainly endemic in Aseer province in the southwest (90) while L. major is reported from Hail, Al-Hasa, Eastern, and the Riyadh provinces (91,92).…”
Section: Saudi Arabiamentioning
confidence: 99%
“…Saudi Arabia is another important focus of CL (89), with most cases occurring in southwest, central, and eastern parts of the country. L. tropica is mainly endemic in Aseer province in the southwest (90) while L. major is reported from Hail, Al-Hasa, Eastern, and the Riyadh provinces (91,92).…”
Section: Saudi Arabiamentioning
confidence: 99%
“…However, L. tropica infection has been herein molecularly diagnosed for the rst time in humans and dogs in the central part of the Saudi Arabia since it was previously reported in the west and southern west of Saudi Arabia in association with the distribution of the sand y species (i.e., distribution of Phlebotomus sergenti), which is a proper vector for that species [27]. Conversely, L. major is more prevalent throughout the country and can be found in the open deserts regions of Saudi Arabia [2,28]. Previous studies in Saudi Arabia have reported the natural infection of L. major in dogs using enzymatic biochemical methods [29,30], though no clinical information was available, nor serology or molecular con rmation were performed.…”
Section: Discussionmentioning
confidence: 85%
“…Of the 25 species of Phlebotomus (P) reported in Saudi Arabia only ve (i.e., P. papatasi, P. sergenti, P. bergeroti, P. kazeruni, and P. arabicus) have been incriminated as vectors of CL [27,28,33,34]. Of these, P. papatasi is the major, and most predominant vector species for L. major [28,33], while P. sergenti is the natural vector species for L. tropica [27]. Presence of P. papatasi and P. sergenti in Al-Qaseem province suggests that they could have a potential role in the transmission of human and canine leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, Ph. papatasi is the main and most predominant vector species for L. major [28,33], while Ph. sergenti is the natural vector species for L. tropica [27].…”
Section: Discussionmentioning
confidence: 99%